APLIKASI DATING PB-210 UNTUK ESTIMASI LAJU SEDIMENTASI MUARA CIGEDE DAN CIOMAS PADA DAERAH TANGKAPAN WADUK MALAHAYU - BREBES - Tommy Hutabarat (Universitas Nasional, 2016)
THE APPLICATION OF PB-210 DATING TO ESTIMATION THE SEDIMENTATION RATE OF CINANGKA AND CIRENGIT ESTUARY ON DARMA - WATERSHED. The application of Pb-210 dating to estimation the rate of sedimentation on the estuary of Cigede and Ciomas reservoirs of Malahayu has been done. Sampling sediment was carried out using a coring tool with diameter of 5 cm and a length of 2 m at the depth to 30 cm, then each 2 cm thickness of samples was sliced. Before the measurement of Pb-210, samples were prepared chemically. The measurement of Pb-210 was performed using gamma and alpha spectrometry. The results obtained sedimentation rate for Ciomas and Cigede estuary were of 1,04 cm/year and 1,23 cm / year, respectively . This research was carried out in order to erosion study using natural isotope of Cs-137 through activities of Block Grant 2011 in Malahayu - Brebes reservoirs.